HEV-ORF3 Encoding Phosphoprotein Interacts With Hepsin - Wang, Chunyan (Kowsar, 2014)
BACKGROUND: Hepatitis E virus (HEV) is a major causative agent of acute clinical hepatitis in adults through much of Asia, the Middle East and Africa. Open reading frame 3 (ORF3) encodes around 120 amino acids of phosphorylation protein that associates with the cytoskeleton, while its precise biological function is still unknown. OBJECTIVES: In order to understand the function of ORF3 protein (pORF3) in depth, HEV ORF3 interacting proteins were screened in human hepatocytes cDNA library using two-hybrid system techniques and further verification of the interactions were carried out through co-immunoprecipitation (Co-IP). MATERIALS AND METHODS: The Cyto-Trap two-hybrid system technology, a classical method for analyzing protein interactions, was used to screen the pORF3 interacting proteins from human hepatocytes cDNA library. RESULTS: Through the Cyto-Trap two-hybrid system, eight proteins interacting with pORF3 were winnowed. The Co-IP results confirmed that hepsin which is reported to function as the inhibitor of several tumors reacted with pORF3. CONCLUSIONS: Out of eight screened proteins interacting with pORF3, hepsin was confirmed to have specific interactions with pORF3.